High-throughput quantification of protein structural change reveals potential mechanisms of temperature adaptation in Mytilus mussels - Chao, Ying-Chen; Merritt, Melanie; Schaefferkoetter, Devin; Evans, Tyler G. (BMC ecology and evolution, 2020)
Temperature exerts a strong influence on protein evolution: species living in thermally distinct environments often exhibit adaptive differences in protein structure and function. However, previous research on protein temperature adaptation has focused on small numbers of proteins and on proteins adapted to extreme temperatures. Consequently, less is known about the types and quantity of evolutionary change that occurs to proteins when organisms adapt to small shifts in environmental temperature. In this study, these uncertainties were addressed by developing software that enabled comparison of structural changes associated with temperature adaptation (hydrogen bonding, salt bridge formation, and amino acid use) among large numbers of proteins from warm- and cold-adapted species of marine mussels, Mytilus galloprovincialis and Mytilus trossulus, respectively. Small differences in habitat temperature that characterize the evolutionary history of Mytilus mussels were sufficient to cause protein structural changes consistent with temperature adaptation. Hydrogen bonds and salt bridges that increase stability and protect against heat-induced denaturation were more abundant in proteins from warm-adapted M. galloprovincialis compared with proteins from cold-adapted M. trossulus. These structural changes were related to deviations in the use of polar and charged amino acids that facilitate formation of hydrogen bonds and salt bridges within proteins, respectively. Enzymes, in particular those within antioxidant and cell death pathways, were over-represented among proteins with the most hydrogen bonds and salt bridges in warm-adapted M. galloprovincialis. Unlike extremophile proteins, temperature adaptation in Mytilus proteins did not involve substantial changes in the number of hydrophobic or large volume amino acids, nor in the content of glycine or proline. Small shifts in organism temperature tolerance, such as that needed to cope with climate warming, may result from structural and functional changes to a small percentage of the proteome. Proteins in which function is dependent on large conformational change, notably enzymes, may be particularly sensitive to temperature perturbation and represent foci for natural selection. Protein temperature adaptation can occur through different types and frequencies of structural change, and adaptive mechanisms used to cope with small shifts in habitat temperature appear different from mechanisms used to retain protein function at temperature extremes.